Effects of river discharge and the California Current on pycnocline depth at the eastern entrance to the Gulf of California. (15th February 2021) - Serrano, David; Valle-Levinson, Arnoldo
Abstract: Monthly hydrographic data were obtained at one station for 4 years at the eastern entrance to the Gulf of California to determine the influence on the pycnocline of waters from river discharge or from the California Current. Data were collected from 2005 to 2009, 20 km offshore over a depth of 127 m on the continental shelf in the vicinity of the Tropic of Cancer. The 4-yr average of the maximum surface temperature was 30.01 °C and the minimum was 21.07 °C, with an absolute minimum of 18.32 °C in January 2008. For salinity, the 4-yr average of the maximum salinity was 35.35 g/kg. Most remarkably, an absolute minimum salinity of 31.08 g/kg was recorded in October 2018 due to freshwater runoff. Waters from the California Current were detected between 35 and 105 m depth from August to September during the four years of observations. Anomalies in sea surface height, with amplitude of centimeters, were associated to pycnocline base oscillations (isotherm of 18 °C) with an amplification factor of 250. The isotherm of 18° was correlated (r = -0.9) to the coefficients of the first empirical mode, which explained 90% of the temperature variance. Highlights: Continental runoff suggests the formation of low-density waters that extend superficially on the continental shelf. Waters of the California Current can reach the region between 35 m and 105 m. The fluctuations of the SSH were produced by steric height (78%) and by atmospheric pressure (19%).